2013
DOI: 10.1371/annotation/4afd48b1-8dc0-47cc-9c8a-99aba7623116
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Netazepide, a Gastrin Receptor Antagonist, Normalises Tumour Biomarkers and Causes Regression of Type 1 Gastric Neuroendocrine Tumours in a Nonrandomised Trial of Patients with Chronic Atrophic Gastritis

Abstract: Introduction: Autoimmune chronic atrophic gastritis (CAG) causes hypochlorhydria and hypergastrinaemia, which can lead to enterochromaffin-like (ECL) cell hyperplasia and gastric neuroendocrine tumours (type 1 gastric NETs). Most behave indolently, but some larger tumours metastasise. Antrectomy, which removes the source of the hypergastrinaemia, usually causes tumour regression. Non-clinical and healthy-subject studies have shown that netazepide (YF476) is a potent, highly selective and orally-active gastrin/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Similarly, carcinogenesis in M. natalensis is enhanced by the histamine 2 receptor antagonist (H2RA) loxtidine [30], but inhibited by NTZ [31] and likewise gastric carcinogenesis in hypergastrinemic transgenic INS-GAS mice is inhibited by NTZ [32]. In patients with hypergastrinemia due to chronic atrophic gastritis, we have reported that NTZ can eradicate (type 1) ECL cell NE tumors (NETs) [33][34][35]. Interestingly, patients with chronic atrophic gastritis have an increased risk of both gastric adenocarcinomas and NETs [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, carcinogenesis in M. natalensis is enhanced by the histamine 2 receptor antagonist (H2RA) loxtidine [30], but inhibited by NTZ [31] and likewise gastric carcinogenesis in hypergastrinemic transgenic INS-GAS mice is inhibited by NTZ [32]. In patients with hypergastrinemia due to chronic atrophic gastritis, we have reported that NTZ can eradicate (type 1) ECL cell NE tumors (NETs) [33][34][35]. Interestingly, patients with chronic atrophic gastritis have an increased risk of both gastric adenocarcinomas and NETs [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of enterochromaffin-like (ECL) cells of the gastric corpus and fundus is stimulated by gastrin and most gastric neuroendocrine tumours (NETs) develop due to long-term hypergastrinemia. Gastric NETs develop in patients with autoimmune chronic atrophic gastritis (CAG) (type 1), as well as in patients with gastrinomas (type 2), and type 1 gastric NETs regress after treatment with a gastrin receptor antagonist [1,2]. The main risk factor for gastric adenocarcinomas is Helicobacter pylori infection with extensive atrophic gastritis [3] that leads to gastric hypoacidity.…”
Section: Introductionmentioning
confidence: 99%